Combustion Characteristics of Low Calorific Value Biogas and Reaction Path of NOx Based on Sensitivity Analysis - Zuo, Zongliang; Qi, Chuanjia; Ma, Jinshuang; Sun, Huiping; Luo, Siyi; Ren, Dongdong; Zhang, Yifan; Guo, Jianxiang; Cheng, Zhanjun; Li, Chang (Frontiers in Chemistry, 2022)
The combustion mechanism of biogas mixture is unclear, which leads to the lack of basis for the control of operating parameters. Combustion characteristics and reaction path of typical low calorific value biogas with variation of preheating temperature and air equivalence ratio (Φ) are discussed in this paper. Preheating can not only improve the flame propagation speed and flame temperature, but also increase the proportion of NO in the product at the end of combustion flame. To some extent, improving combustion efficiency and NOx control are contradictory operating parameters. The amount of NO increases with the increase of flame distance. The maximum value of NO appears when Φ is 1.1. NO formation rate is improved by preheating of the biogas. And the paths of N2 → N2O →NO, N2 → NNH →NO and N2 →NO) are all enhanced. When the equivalence ratio changes from 1.0 to 0.8, NO formation rates decrease.